35.9k views
3 votes
Zuleika was solving 2(x - 3) - 9 = 3x - 9. Zuleika's first step resulted in 2(x - 3) = 3x

because she used the multiplication/addition property of equality. The second

step resulted in 2x - 16 = 3x because she collected like terms used the distributive

properly. In the next two steps, Zuleika used the addition/multiplication property

twice to get -x = 6.She then found the solution, x = -6, by using the

addition/multiplication property of equality.

User Razzie
by
7.4k points

1 Answer

6 votes

Answer:


x=-6

Explanation:

The given equation is


2(x-3)-9=3x-9

Step 1: Using addition property of equality, add 9 on both sides.


2(x-3)-9+9=3x-9+9


2(x-3)=3x

Step 2: Using distributive property, we get


2(x)+2(-3)=3x


2x-6=3x

Step 3: Using addition property of equality twice we get


2x-6+6=3x+6


2x=3x+6


2x-3x=3x+6-3x


-x=6

Step 4: Using multiplication property of equality, multiply both sides by -1.


(-x)(-1)=(6)(-1)


x=-6

Therefore, the solution of the given equation is x=-6.

User Yooakim
by
8.5k points